Prevalence of caries and social classes in a group of children under 6 years old in southern Chile - Gloria Analia González Nieto (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Background: in Chile there are high rates of decay. The emergence of this condition is influenced by social determination, reflected in low income, unfavorable physical environment, unhealthiness and low education. Objective: to determine the prevalence of caries in children under 6 years of age and correlate it with social stratification. Methods: retrospective study on children admitted for dental treatment during 2018 at the San Sebastián University Health Center. Clinical records were reviewed and 44 records were analyzed. The ceod index and social risk survey of Graffar attached were taken into account. The data was recorded in Excel® and then exported to the SPSS program for statistical analysis. Results: the study population was 44 children, 24 boys (54.5%) and 20 girls (45.5%). The prevalence of caries was 31.8%. The distribution of caries in males was 85.2% and in females 14.8%. According to Graffar's stratification, 47.7% belongs to the Medium High stratum, 50% to the Medium Low stratum and 2.3% to the Labor stratum. Children with cavities are in the upper middle and lower middle strata. Conclusion: the prevalence of caries is high in the upper middle and lower middle strata. There were differences between males and females. There were no significant differences regarding the profession of the family head, mothers´ educational levels, and income and housing conditions.